Tuberculosis Suspect in the Companies in Semarang District Indonesia; Case-Control Study (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
In Semarang district, the population at the companies were 83120 workers. The number of smear positive cases in 2011 were 258 and 3898 suspected tuberculosis. Case-control study was conducted to analyze the risk of TB suspect infection among workers in the factory. We recruited 194 suspects and 197 controls who visited the factory clinic. The most common symptom was coughing with sputum (63 %) and then followed by malaise, chest pain, sweating at night, weight loss, dyspnea, anorexia, cough more than 2 weeks, sub febris and hemoptoe. Around 47 % both of the suspects and controls don’t know received Bacillus Calmette-guérin (BCG) or not. The multivariate analysis showed the dominant factors that influence the occurrence of TB suspect, “education”, “income”, “ashamed of having TB”, “TB treatment is very costly”, and “share dish”.distribution of health education booklet to teachers and parents.